Mobile Point of Sales (Mi-POS) Application for Cashiers Using React Native Framework A Case Study at Fajar Jaya Snack Shop - Dimas Fajar Saputro; Dedi Gunawan (Jurnal Ecotipe (Electronic, Control, Telecommunication, Information, and Power Engineering), 2023)
Toko Snack Fajar Jaya was a store that sold snacks in both bulk and retail. The store's current system still relied on manual bookkeeping, causing errors and uncertainties in data management and sales reports. To solve these problems, a mobile application called Mi-POS was developed using React Native to facilitate the development process. The application could record transactions, view transaction history, manage product inventory, and print receipts. The SDLC method was used in developing the application, and it was tested using Black-box Testing and the System Usability Scale (SUS) to evaluate its quality and effectiveness. Results from Black-box Testing showed that all features ran smoothly with an error rate of 0%. Meanwhile, SUS testing showed a score of 63.4, which falls in the "OK and usable" category.